Um aporte ao porvir do caso Gomes Lund e outros (Guerrilha do Araguaia) Vs. Brasil, à luz da argumentação jurídica argentina articulada na causa ‘Simón’, no âmbito do Sistema Interamericano de Proteção dos Direitos Humanos - Flores, Maria José (2016)
This investigative research has been prepared based on the judgment of the Inter-American Court of Human Rights of November 24, 2010, issued in the case Gomes Lund. In it, the Inter-American Court finds, unanimously, the international responsibility of the Brazilian State for the enforced disappearance of members of the Guerrilla do Araguaia and violation of multiple human rights of the direct victims of disappearance, their families and Brazilian society as a whole. One of the central aspects of the judgment is it statement toward the ineffectiveness of the Amnesty Law (1979), thus eliminating the main obstacle that prevents the search for justice in domestic courts. However, in the Brazilian domestic level, the Supreme Federal Court reached a majority agreement within the framework of a constitutional action (complaint action of non-compliance of fundamental n°153, 2010), by which it declared that the Brazilian Amnesty Law is not subject to review, that it legal status is a quasi-law (law-measure) under which lacks the ability to be interpreted by a court of law. Notwithstanding which, the judgment of the majority in a new, mistaken and falsely way extended its scope until making match the Amnesty Law with the source from which emanates the legitimacy of the Brazilian constituent (1988). In other words, Brazilian democracy – this say by the highest authority of the judiciary of this country – is founded and based on impunity for serious violations of human rights and crimes against humanity committed during the state terrorism that hit Brazil in its recent past. In order to reaffirm the juridical unsustainability of the decision of the Brazilian Supreme Court already mentioned, this research is based on the hypothesis that the violation of human rights inevitably implies a violation of constitutional order, national and international. And this is so because the contemporary notes of human rights and the institutionalization of universal jurisdictions with a mandate to protect and promote them converge with regulatory and internal jurisdictions in the structural space of law. For this, through three chapters, is develop first, the conception of human rights that traces this investigative perspective and its housing in the core of universal institutional processes: culture and democracy. Second, this perspective is confronted with the practice of the organs of the Inter-American System of Human Rights, which is approached from the angle of the contentious jurisdiction of the Commission and Inter-American Court. Finally, the Inter-American patterns or standards are analyzed - inaugural, central and arguably consolidated for decades at the regional level - in the field of forced disappearance of persons, and illustrated its correct juridical incorporation by the judgment of the Supreme Court of Argentina in the cause Simón (2005). The study aims to demonstrate or rather reaffirm that the Federative Republic of Brazil is in possession of the juridical elements that will allow the country to fully comply with the judgment of the Inter-American Court pronounced in the case Gomes Lund and which is still pending compliance. That is, ultimately, this research bet, that Gomes Lund case will have a future; future that will have repercussions on the functioning of Justice, the strengthening of Social Democracy and the rule of law consolidation in Brazil. This research is conducted through the analytical method and the case study method.